2023
DOI: 10.1007/s11270-023-06432-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicological Effects of ZnO and CuO Nanoparticles with Taraxacum officinale as Bioindicator

Abstract: Nanoparticles are rising worries because of recent reports about potential toxicity amid the incorporation of these emerging materials into consumer products, and industrial and scientific applications. New developments in the automotive industry are incorporating novel materials, which have increased the emission of nanoparticles into the atmosphere. To overcome the difficulty of detecting and characterizing atmospheric nanoparticles, alternative methods have been proposed, just as the indirect detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Similarly, iron oxide NPs were more toxic to the plant Oenothera biennis than the bulk form, resulting in changes in the antioxidant and physiological systems [9]. Higher genotoxic effect was also found in the plant Taraxacum officinale exposed to copper oxide and zinc oxide NPs compared to their corresponding bulk counterparts [46]. However, in this study, bulk MoS2 induced more toxic effects on E. crypticus and F. candida compared with 2D MoS2 NPs.…”
Section: Nanoparticle Versus Bulk Effects-an Overviewmentioning
confidence: 44%
See 1 more Smart Citation
“…Similarly, iron oxide NPs were more toxic to the plant Oenothera biennis than the bulk form, resulting in changes in the antioxidant and physiological systems [9]. Higher genotoxic effect was also found in the plant Taraxacum officinale exposed to copper oxide and zinc oxide NPs compared to their corresponding bulk counterparts [46]. However, in this study, bulk MoS2 induced more toxic effects on E. crypticus and F. candida compared with 2D MoS2 NPs.…”
Section: Nanoparticle Versus Bulk Effects-an Overviewmentioning
confidence: 44%
“…Thus, NPs interact with biological systems through different mechanisms of action and normally have different tissue distribution patterns than their bulk form, resulting in higher toxicity [44]. Indeed, numerous studies have demonstrated that, once in the environment, nanomaterials are more toxic to organisms than their corresponding bulk counterparts [9,45,46]. A previous study with MoS 2 nanosheets showed that the NPs form induced a higher level of toxicity than bulk MoS 2 micromaterial, resulting in oxidative stress to soil bacteria Bacillus cereus and Pseudomonas aeruginosa [45].…”
Section: Nanoparticle Versus Bulk Effects-an Overviewmentioning
confidence: 99%
“…125). 19,32–38 Therefore, the chances of ZnO and CuO NPs entering into natural waters, streams, and wastewater are very high. 39 Corresponding metal ion toxicity of ZnO and CuO nanoparticles has already been characterized.…”
Section: Introductionmentioning
confidence: 99%